Evaluating Government Policy of Monitoring NGOs in Pakistan - Nisa, Fatima; Kamran, Muhammad; Mahsood, Asma Khan (Mediterranean Journal of Social Sciences, 2021)
Non profitable organizations have been contributing in the development of state and society for a long time. These are generally praised for their progressive agendas. However, occasionally these have also been blamed for having some hidden agenda. This requires strict monitoring and evaluation of this sector. Different policies have been introduced in the past for this purpose. However, some of them have been found to be working for foreign agendas. Therefore, it is extremely important to comprehend the effectiveness of the monitoring and evaluation policies in Pakistan. This paper is focused on different monitoring and evaluation policies and compared it with the policy of PML (N) government (2013-18) to bring to limelight the strengths and weakness of such policies. The research paper is primarily designed to find out comprehensive study that how the government presently monitored the working of NGOs. The analysis will help the policy makers to evaluate the working of NGOs in an effective way. Received: 28 October 2020 / Accepted: 5 December 2020 / Published: 17 January 2021